Immunotherapy and Targeted Therapy for Advanced Gastroesophageal Cancer: ASCO Guideline. Issue 7 (1st March 2023) - Shah, Manish A.; Kennedy, Erin B.; Alarcon-Rozas, Ashley E.; Alcindor, Thierry; Bartley, Angela N.; Malowany, Aubrey Belk; Bhadkamkar, Nishin A.; Deighton, Dana C.; Janjigian, Yelena; Karippot, Asha; Khan, Uqba; King, Daniel A.; et al.
Abstract : PURPOSE: To develop recommendations involving targeted therapies for patients with advanced gastroesophageal cancer. METHODS: The American Society of Clinical Oncology convened an Expert Panel to conduct a systematic review of relevant studies and develop recommendations for clinical practice. RESULTS: Eighteen randomized controlled trials met the inclusion criteria for the systematic review. RECOMMENDATIONS: For human epidermal growth factor receptor 2 (HER2)–negative patients with gastric adenocarcinoma (AC) and programmed death-ligand 1 (PD-L1) combined positive score (CPS) ≥ 5, first-line therapy with nivolumab and chemotherapy (CT) is recommended. For HER2-negative patients with esophageal or gastroesophageal junction (GEJ) AC and PD-L1 CPS ≥ 5, first-line therapy with nivolumab and CT is recommended. First-line therapy with pembrolizumab and CT is recommended for HER2-negative patients with esophageal or GEJ AC and PD-L1 CPS ≥ 10. For patients with esophageal squamous cell carcinoma and PD-L1 tumor proportion score ≥ 1%, nivolumab plus CT, or nivolumab plus ipilimumab is recommended; for patients with esophageal squamous cell carcinoma and PD-L1 CPS ≥ 10, pembrolizumab plus CT is recommended. For patients with HER2-positive gastric or GEJ previously untreated, unresectable or metastatic AC, trastuzumab plus pembrolizumab is recommended, in combination with CT. For patients with advanced gastroesophageal or GEJ AC whose disease has progressed after first-line therapy, ramucirumab plus paclitaxel is recommended. For HER2-positive patients with gastric or GEJ AC who have progressed after first-line therapy, trastuzumab deruxtecan is recommended. In all cases, participation in a clinical trial is recommended as it is the panel's expectation that targeted treatment options for gastroesophageal cancer will continue to evolve. Additional information is available at www.asco.org/gastrointestinal-cancer-guidelines .